2020
DOI: 10.3390/app10155178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inspiratory Muscles Training Plus Rib Cage Mobilization on Chest Expansion, Inspiratory Accessory Muscles Activity and Pulmonary Function in Stroke Patients

Abstract: After stroke, limited ribcage movement may lead to impaired respiratory function. Combining threshold inspiratory muscle training with rib cage joint mobilization has been shown to enhance the recovery of respiratory function in patients with stroke. The present study investigated whether the combination of rib cage joint mobilization and inspiratory muscle training would improve chest expansion, inspiratory muscle activity, and pulmonary function after stroke. Thirty stroke patients were recruited and randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Our findings are supported by Hernández-Álvarez et al, who investigated the effect of 8 weeks of respiratory muscle training using threshold IMT on lung function and respiratory muscle strength in sedentary young people and discovered a significant change in FEV1, which was associated with a noticeable improvement in respiratory muscle strength [39]. Park also concluded that inspiratory muscle training in combination with rib cage mobilization is effective in improving chest wall movement, pulmonary function, chest expansion, and inspiratory muscle strength [40]. In addition, Rehman et al, found that passive stretching of the respiratory muscles can effectively benefit the status of such individuals, particularly in terms of chest expansion and functional capacity.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings are supported by Hernández-Álvarez et al, who investigated the effect of 8 weeks of respiratory muscle training using threshold IMT on lung function and respiratory muscle strength in sedentary young people and discovered a significant change in FEV1, which was associated with a noticeable improvement in respiratory muscle strength [39]. Park also concluded that inspiratory muscle training in combination with rib cage mobilization is effective in improving chest wall movement, pulmonary function, chest expansion, and inspiratory muscle strength [40]. In addition, Rehman et al, found that passive stretching of the respiratory muscles can effectively benefit the status of such individuals, particularly in terms of chest expansion and functional capacity.…”
Section: Discussionsupporting
confidence: 85%
“…The maximum voluntary expiration entails the shortening of the abdominal muscles, and the FVC, PEF, and FEV1 are dependent on it. In a previous study, spine mobilization applied on the rib cage to increase the inspiratory capacity of stroke patients increased the inspiratory muscle activity but had no effect on pulmonary function [ 48 ]. This result supports the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…The rib cage circumference was measured horizontally using a tape measure with the help of marked reference points. Upper and lower chest expansions were performed three times and the mean value was used (Bockenhauer et al., 2007; Park, 2020).…”
Section: Methodsmentioning
confidence: 99%